Strategi Pengembangan Wisata Kolam Renang Alam Tilanga’ di Kelurahan Sarira Kecamatan Makale Utara Kabupaten Tana Toraja - Efrain Owen Taruk; Abedneigo Carter Rambulangi; Mince Batara (CV. Ulil Albab Corp, 2024)
Strategy for developing the Tilanga' Natural Swimming Pool tourist attraction in Sarira sub-district, North Makale District, Tana Toraja Regency.